The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.2320/matertrans.mra2007603
|View full text |Cite
|
Sign up to set email alerts
|

Standard Gibbs Energy of Formation of Mg<SUB>3</SUB>La Determined by Solution Calorimetry and Heat Capacity Measurement from Near Absolute Zero Kelvin

Abstract: The standard Gibbs energy of formation, Á f G o T , of Mg 3 La in the temperature range from near absolute zero Kelvin to 525 K were determined by calorimetry. The heat capacities, C p , from 2 K to 525 K were measured by the relaxation method and DSC. The Á f G o T (Mg 3 La) values were determined by combining the C p data with the standard enthalpy of formation at 298 K which was measured by the Calvet-type calorimeter using hydrochloric acid solution. From 2 to 350 K, the Á f G o T increases gradually, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 17 publications
2
13
0
Order By: Relevance
“…8a-c show the predicted C p (T ) for the cubic La-Mg compounds. The PBEsol results are in closer accord with experimental data from the literature for LaMg [51] and LaMg 3 [56]. However, all three figures suggest only very minimal differences between the PBE and the PBEsol.…”
Section: Bulk Modulussupporting
confidence: 90%
See 1 more Smart Citation
“…8a-c show the predicted C p (T ) for the cubic La-Mg compounds. The PBEsol results are in closer accord with experimental data from the literature for LaMg [51] and LaMg 3 [56]. However, all three figures suggest only very minimal differences between the PBE and the PBEsol.…”
Section: Bulk Modulussupporting
confidence: 90%
“…It has been shown to absorb hydrogen to 4 wt.% at 300 • C [6]. Buschow found that LaMg 3 is a Pauli paramagnet [55] and Yamamoto et al [56] observed that the LaMg 3 valence band consists primarily of free electron gas-like Mg electrons with strongly localized 4f electrons from La. LaMg 3 has a narrow composition range at high temperatures [57].…”
Section: Structures and Known Propertiesmentioning
confidence: 98%
“…(3), Δ f E total, T can be determined. Because the Δ f H 298o values for the compounds have been determined by the acid solution calorimetry in our previous studies 11–15 as shown in Table I, these values were inserted into Eq. (3) in the present study.…”
Section: Data Analysis To Determine Formation Energies δFetotal mentioning
confidence: 99%
“…(3) in the present study. The Δ f H 298o values include inevitably experimental error of ±3 kJ mol −1 , described in our previous studies 11–15.…”
Section: Data Analysis To Determine Formation Energies δFetotal mentioning
confidence: 99%
See 1 more Smart Citation